Elodeoidins A–H, acylphloroglucinol meroterpenoids possessing diverse rearranged skeletons from Hypericum elodeoides. Issue 7 (23rd October 2020) - Li, Qi-Ji; Tang, Peng-Fei; Zhou, Xin; Lu, Wei-Jia; Xu, Wen-Jun; Luo, Jun; Kong, Ling-Yi
Abstract : Inspired by the biosynthetic fragment (9 ), the first example of rearranged dimethylated acylphloroglucinol and monoterpene adducts, elodeoidins A–H (1–8 ) representing four skeletons and two rearranged pathways were authenticated from H. elodeoides . Abstract : Inspired by a geranyl-originated undecanoate acid ethyl ester (biosynthetic fragment, 9 ), elodeoidins A–H (1–8 ), representing four unprecedented rearranged acylphloroglucinol meroterpenoids, were discovered from the herb of Hypericum elodeoides . Their structures were elucidated by HRESIMS, NMR, Mosher, ECD, quantum chemical calculations, and biosynthetic pathways. Structurally, the six-membered acylphloroglucinol core rearranged to a five-membered β-diketone unit possessing an exocyclic carbonyl group (C-1 or C-3) through an α-ketol rearrangement. Subsequently, key cyclizations with C-1 or C-3 established a 2-cyclopentyltetrahydrofuran moiety in 1 and 2, a [5, 5]-spiroketal-fused 5–5–5–5 skeleton in 3 and 4, a 1, 2-dioxonane-bridged 5–9–5 framework in 5 and 6, and a 2, 5-dioxabicyclo[2.2.2]octane caged structure in 7 and 8 . (±)-5 and 6 showed significant anti-inflammatory activity (IC50 : 6.06 ± 0.41–10.46 ± 0.14 μM). These diversiform skeletons indicated that the biosynthetic fragment inspired discovery and elucidation strategy is valuable for the discovery of novel and unprecedented natural products.